Impacts of gap planting on soil density and erosion - Elias Elias; Ujang Suwarna (Jurnal Penelitian Kehutanan Wallacea, 2019)
By 2016, there were 32.70 million ha of degraded forests in Indonesia. If it isnot quickly rehabilitated, there will be land use changes and expansion of industrial forest plantation, which significantlyaffects itsbiodiversity and environmental. This research aims to study the impacts of the gap planting technique with red jabon on soil density and erosion. The research used: (1) the gap planting technique of red jabonwitha proportion of the total gap area to thetotal natural forest area of 40%: 60%, planting distance of 4m x 5m, and the number of trees planted of 200 stems/ha, (2) Digital-Humboldt Static Cone Penetrometer to measure soil density, and (3) stick for soil erosionmeasurement. The results showed that gap planting with red jabon to rehabilitate degraded natural forests increasedthe soil density, but itsvalue was categorized as a very loose soil class. On the other hand, the soil erosionin gap area was lower than in degraded natural forest area, because the condition of a part of the degraded forest was unvegetatedland, and there were the wastes of branches, twigs, and leaves as well as grown grasses on the soil surface that hinder the soil erosion in the gap area. This research concluded, that the impact of the gap planting on soil density can be neglected, and the impact of the gap planting on soil erosion is positive. Further research on social-economic, biodiversity, effective and efficiency aspects of the gap planting technique for forest rehabilitation are needed before its implementation